2021
DOI: 10.3390/foods10102356
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and Environment Affect the Grain Quality and Yield of Winter Oats (Avena sativa L.)

Abstract: The extent to which the quality and yield of plant varieties are influenced by the environment is important for their successful uptake by end users particularly as climatic fluctuations are resulting in environments that are highly variable from one growing season to another. The genotype-by-environment interaction (GEI) of milling quality and yield was studied using four winter oat varieties in multi-locational trials over 4 years in the U.K. Significant differences across the 22 environments were found betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The results of this study, which are consistent with those of earlier investigations (Chohan et al, 2004; Lodhi et al, 2009; Mendoza-Pedroza et al, 2021), show that oat cultivars varied from one another in terms of morphological features. Howarth et al (2021) found that all the traits of oat crops are significantly influenced by the environment, hence environmental factors and varietal characteristics may both contribute to the variation in morphological traits among oat varieties (Pant et al, 2022; Singh et al, 2018). Hence, the adaptability of different oat varieties to a given environment differs, also due to genetic variations that affect hormonal balance and cell division rate (Zaman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study, which are consistent with those of earlier investigations (Chohan et al, 2004; Lodhi et al, 2009; Mendoza-Pedroza et al, 2021), show that oat cultivars varied from one another in terms of morphological features. Howarth et al (2021) found that all the traits of oat crops are significantly influenced by the environment, hence environmental factors and varietal characteristics may both contribute to the variation in morphological traits among oat varieties (Pant et al, 2022; Singh et al, 2018). Hence, the adaptability of different oat varieties to a given environment differs, also due to genetic variations that affect hormonal balance and cell division rate (Zaman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely caused by different temperature accumulation; grain formation needs a higher temperature than hay production does. Generally, oat hay is harvested at milk stage, and a study also reported that harvesting in the late heading stage would increase the hay yield, 49 whereas oat grain is harvested in the fully ripe stage when grain moisture reaches 15% 50 . However, owing to data paucity, this study incorporated MAP and MAT rather than growing‐season precipitation or temperature during important phases of oat growth, which is critical in interpreting the effect of water on oat production.…”
Section: Discussionmentioning
confidence: 99%
“…The overall relationship between phenology and crop yield, through adaptation and yield potential, is not limited to Australian context. For example, phenology is a driver of yield in North American and European climates (Yan et al, 2007;Howarth et al, 2021).…”
Section: The Importance Of Phenology To Oat Adaptionmentioning
confidence: 99%
“…Similarly, phenology is an important component of optimisation of oat for different end uses. For example, the timing of maturation influences quality of milling oats (Howarth et al, 2021). Interactions between phenology and seasonal conditions also influence forage oat quality (Coblentz et al, 2012;Ki-Seung et al, 2014).…”
Section: The Importance Of Phenology To Oat Adaptionmentioning
confidence: 99%